Macroclinium chasei (Orchidaceae, Oncidiinae): a new record for Brazil - Engels, Mathias E. (2017)
We present a new record for Brazil, Macroclinium chasei, until now known only from Bolivia and Peru. A description, illustration and photographs are presented, together with data of geographic distribution, and taxonomical and ecological comments.